Soberania e tributação: implicações na competência tributária - Marcelo, Eliana Borges de Mello (2016)
This work has as objective the analysis of taxation authorized by the Constitution to the governmental entities sided by implications related to sovereignty, both internal and external, in this contemporary world. The starting premise is that the State powers come as expressed in the Constitution, being sovereignty a State value granted by people. This rhetoric approach reaches an overview on theory of values, as the base for the juridical principles, with emphasis to the tax related ones and their legitimating sources. The concepts of the expression tax are herewith presented as well as its various doctrinal classifications, briefly enumerating the taxes presented by the constitutional text, establishing the correlation between sovereignty and taxation sources. Last, sovereignty is faced to globalization, dictated by the international law, treaties and the various organisms which legitimate imposed behaviors towards the tending institution of a global constitutionalism, remarking community groups like the European Union and MERCOSUL